Analysis of intelligent green building policy and developing status in Taiwan. (August 2016) - Kuo, Chung-Feng Jeffrey; Lin, Chieh-Hung; Hsu, Ming-Wen
Abstract: In 2010, Taiwan launched a program dubbed "four emerging intellectual industries" that lists intelligent green buildings. The aim of promoting of intelligent green building is to stimulate the architecture technology industry. This has been combined with Information and Communication Technology (ICT) and the concept of green building to provide a safe and healthy living environment. While doing this it will also aim to reduce carbon emissions and save energy. This study investigates intelligent green building policies and the promotion of progress in Taiwan. It probes into cases from 1988 to 2014. Key success factors are derived from analyzing and summarizing intelligent green building experiences in Taiwan. This is done through Secondary Data Analyses by: 1. Establishing clear norms and standards for intelligent green building design and improvement; 2. First carrying out policies in public sector, in order to provide field trial and safeguarded market opportunities for industries; 3. Implementing rating-based assessments, in order to raise the quality of design; 4. Mandatory or incentive policies are introduced, depending on local specialties and conditions; 5. Respectively planning incentives for relevant interested parties in industrial chain; 6. Strengthening marketing efforts and proactively promoting policies. Highlights: Aggregate and analyze the results of Intelligent Green Building policy in Taiwan. Chi-square Test of Independence is used for inspecting successful factors. Organize experiences and propose recommended feasible scheme for future.